Differences in salivary acidity before and after consumption of sugary drinks in children of Ra Hudallah Kujangsari Village, Langensari Subdistrict, Banjar City: Perbedaan derajat keasaman saliva sebelum dan sesudah konsumsi minuman manis pada anak-anak Ra Hudallah Desa Kujangsari Kecamatan Langensari Kota Banjar - Mellinia, Patricia Octaviane; Zalzamitha, Tifanny; Posumah, Gabriela Lestari Natalya; Sinaga, Nadya Atalia; Setiawan, Ignatius; Laksmi, Primarizka Iswara; Sugiaman, Vinna Kurniawati (Makassar Dental Journal, 2024)
This study aims to determine the effect of sugary drinks on the pH value of saliva in children, is an analytical observation with expe-rimental methods regarding the relationship of sugary drinks to the pH value of saliva measured using a pH meter. The research was conducted at RA Hudallah Kujangsari Village, Langensari Subdistrict, Banjar City. The results showed that before drinking sugary drinks, the majority of children had a normal pH category (64%), while after drinking sugary drinks, the pH state changed to be more acidic (70%) and only 22% had a normal pH category. It was concluded that after drinking sugary drinks, 78% expe-rienced a significant decrease in salivary pH, the rest had a normal pH.